Does total hip arthroplasty with high hip centre in dysplasia compromise acetabular bone stock?. Issue 3 (May 2023) - Kannan, Arun; Madurawe, Chameka; Pierrepont, Jim; McMahon, Stephen
Background: The placement of uncemented acetabular components during total hip arthroplasty (THA) in Crowe II and Crowe III dysplasia can be at the anatomic or high hip centre position. Purposes: Using computerised tomography data, we simulated acetabular cup placement at the anatomic hip centre and the high hip centre positions to assess whether there is a difference between the 2 in terms of bone loss from acetabular reaming and in acetabular coverage by host bone. Methods: The study population included a consecutive cohort of 19 patients (22 hips) with Crowe II or III dysplasia. 3-dimensional models of the pelvis were created for each patient and digital templating was used to determine the anatomic and high hip centre positions. The coordinates of the digitally templated cup positions were fed into an image processing software to estimate the amount of bone reamed, the cup coverage by host bone and the elevation from tear drop. Results: The mean volume of bone reamed was greater in the high hip centre position as compared to the anatomic position (27.3 ± 11. 4 cm 3 vs. 19.4 ± 12.2 cm 3, p   <  0.0001). The coverage of the acetabular cup by host bone was greater in the high hip centre position (87.3 ± 5.9% vs. 68.3 ± 10%). The mean elevation in the high hip centre group was 13 mm with 3 hips having a breach of the medial wall. Conclusions: In Crowe II and III dysplasia, placement of acetabular cups at the anatomic hip centre better preserves bone stock as compared to high hip centre placement and should be preferred in young patients requiring THA.